A prospective observational comparative study of effectiveness and adverse effects of amitriptyline versus duloxetine in the treatment of somatoform pain disorders in a tertiary care hospital - H., Nagabushan; Monika, P.; H. D., Bhagyavathi (International Journal of Basic & Clinical Pharmacology, 2024)
Background: To compare the effectiveness and adverse effects as well as treatment compliance of amitriptyline and duloxetine in treating somatoform pain disorder. Methods: This study was done on 100 patients, with 50 in each group, at Mandya Institute of Medical Sciences (MIMS) over 6 months. Group A was treated with amitriptyline 75 mg per day, and Group B with duloxetine 40 mg per day. Patient Health Questionnaire (PHQ-15) as well as Social and Occupational Functional Assessment Score (SOFAS) were used to compare effectiveness of treatment. For medication adherence Medication Adherence Rating Scale (MARS) was used. Adverse effects were also monitored. The baseline measurements were taken, and evaluations were conducted at 4th, 8th, and 12th weeks of follow-up. Results: There were 31% males and 69% females. At baseline and after 12 weeks, Group A had average PHQ-15 scores of 14.72±6.13 and 3.16±0.97, respectively, while group B had scores of 17.12±5.45 and 7.22±2.46. During the same period SOFAS scores were 48.70±6.27 and 85.9±5.06 for group A, and 50.86±5.99 and 82.62±6.10 for group B. The effectiveness of Amitriptyline group showed statistically significant difference (p<0.05) when compared with Duloxetine. Group A experienced more adverse effects like dry mouth, drowsiness when compared to Group B. Conclusions: Amitriptyline and duloxetine are effective in treatment of somatoform pain disorder; the effectiveness of amitriptyline was higher when compared to duloxetine in our study.